Form for reporting Iowa Christmas bird counts to Iowa Bird Life, Charles Fuller, December 17, 1988 - Fuller, Charleset al (1988)
Iowa Christmas bird counts of species found in Burlington contributed by Charles Fuller, December 17, 1988. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1988-1989. Epson - sheet feed